Peningkatan Kemampuan Memasang Baju Berkancing Melalui Teknik Modelling pada Murid Disabilitas Intelektual Kelas VI di SLB Negeri Binjai (Indo-MathEdu Intellectuals Journal, 2026)
This study was motivated by the low ability of sixth-grade students with intellectual disabilities to button their clothes independently, as evidenced by their difficulty in adjusting the position of the buttons and buttonholes, thus still requiring assistance from others. This study aims to improve the ability to button clothes through the application of modelling techniques in sixth-grade students with intellectual disabilities at SLB Negeri Binjai. The method used was Classroom Action Research (CAR) with a qualitative and quantitative approach. The research subjects were two sixth-grade students with intellectual disabilities. The research was conducted in two cycles with collaboration between the researcher and the teacher, where each cycle consisted of four meetings. Data collection techniques were carried out through performance tests and observations. Data analysis was conducted using descriptive qualitative and quantitative methods and presented in tables and graphs. The results showed that the application of modelling techniques was able to improve the ability to fasten buttons in both subjects. In cycle I, the abilities of both subjects improved compared to the initial conditions, but one subject did not yet meet the minimum completion criteria. In cycle II, both subjects achieved a minimum mastery level of 75, with scores of 77 and 76 respectively. Based on these results, it can be concluded that the modelling technique is effective in improving the ability to button up clothes in sixth grade students with intellectual disabilities at SLB Negeri Binjai.